2022
DOI: 10.1248/cpb.c22-00466
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Phloridzin against Isoniazid-Rifampicin Induced Liver Injury by Regulating CYP450 and Nrf2/HO-1 Pathway in Mice

Abstract: The protective effect of phloridzin (PHL) and its potential mechanism were examined in mice with liver injury induced by isoniazid (INH) and rifampicin (RFP). The mice were randomly divided into normal control group, model group, low (80 mg/kg), medium (160 mg/kg) and high (320 mg/kg) phloridzin-treated groups. After 28 days treatment, blood and liver tissue were collected and analysed. The results revealed that PHL regulated liver function related indicators and reduced the pathological tissue damage, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, rifampicin induces liver mitochondrial enzymes that reduce serum cyclosporin A levels and may therefore aggravate GVHD ( Wasko et al., 2017 ). In addition, rifampicin was more likely to have adverse reactions when there was liver disease or when it was combined with isoniazid ( Yang et al., 2022 ). Considering the long-term use of tacrolimus for anti-rejection, chronic GVHD and poor liver and kidney functions, rifampicin was not administered, although sensitive to rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“…However, rifampicin induces liver mitochondrial enzymes that reduce serum cyclosporin A levels and may therefore aggravate GVHD ( Wasko et al., 2017 ). In addition, rifampicin was more likely to have adverse reactions when there was liver disease or when it was combined with isoniazid ( Yang et al., 2022 ). Considering the long-term use of tacrolimus for anti-rejection, chronic GVHD and poor liver and kidney functions, rifampicin was not administered, although sensitive to rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that some drugs (such as Naringenin, Phloridzin) have a therapeutic effect on INH+RIF-induced liver injury [ 7 , 8 ], clinically, the treatment of liver injury caused by INH+RIF is still inconclusive. Many compounds in natural plants have been found to be effective in treating various diseases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%